Features of Regularities of Ni[3]Al Intermetallic Compound High-Temperature Synthesis in a Powder Mixture (3Ni+Al) under pressure; Materials Science Forum; Vol. 938 : Materials and Technologies in Mechanical Engineering - Akimov K. O. (2018, 2018)
Title screen